Metoda robnih elementov za dinamiko viskoelastične Maxwellove tekočine - Škerget, Leopold (Strojniški vestnik, 2002)
In this paper we show a numerical scheme based on the boundary-element method (BEM) for the numerical modeling of planar, viskoelastic fluid flows. In particular, the singular-boundary-integral approach, which has been established for the viscous, incompressible flow problem, is modified and extended to include the viscoelastic fluid state. Special attention is given to a proper integration of the conservation and constitutive equations. A velocity-vorticity formulation of the governing equations is adopted. As test cases, non-Newtonian-Maxwell fluid flows in the channels of various geometries are studied.
Keywords: modeli Maxwellovi; modeli robnih elementov; dinamika tekočin; tekočine viskoelastične; reologija; numerični modeli; viskoelastičnost; Maxwellovi modeli